Peran Pendidikan Profesi Guru (PPG) dalam Meningkatkan Profesionalisme Guru Pendidikan Agama Islam - Muhammad trio mahfuzd; Muhammad Jarir; Ajahari Ajahari (Universitas Majalengka, 2026)
The Teacher Professional Education Program (Pendidikan Profesi Guru/PPG) is an educational program designed to prepare prospective teachers and in-service teachers to possess professional competencies in accordance with national education standards. This program serves as one of the government’s efforts to improve the quality of educators, including Islamic Religious Education (PAI) teachers. This article aims to analyze the role of the Teacher Professional Education Program (PPG) in enhancing the professionalism of PAI teachers. The research method used is library research by reviewing various literature sources such as books, journals, and regulations related to teacher professional education. The results of the study indicate that PPG plays an important role in improving the pedagogical, professional, social, and personal competencies of PAI teachers, enabling them to implement more effective learning that is oriented toward character building and the moral development of students.